Factors affecting the price paid for spring-yearling bulls - T.T. Marston; L.E. Wankel; Daniel W. Moser (Kansas Agricultural Experiment Station Research Reports, 2002)
Many factors are considered when commercial cow/calf producers buy bulls. Breeding system needs and breeder's preference determine which breed of bull will be purchased at a multi-breed sale. Our analysis of prices paid for bulls tested and sold through the Kansas Bull Test Station indicates that bull consigners' reputations and marketing techniques influence the price received for bulls at such an event. Individual performance and genetic potential are other areas of interest to bull buyers. Buying habits and prices indicate that commercial cow/calf operations use different traits, depending on the breed, to enhance their cowherd's production.
Keywords: Cattlemen' s Day; 2002; Kansas Agricultural Experiment Station contribution; no. 02-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 890; Beef; Spring-yearling bulls; Price